รูปแบบการจัดการความรู้การเลี้ยงปลาในบ่อดินที่ประสบความสำเร็จในจังหวัดอ่างทอง - สุขะชีวานนท์ กฤตภาส (RMUTSB ACADEMIC JOURNAL, 2016)
การวิจัยมีวัตถุประสงค์เพื่อ 1) ศึกษาการจัดการความรู้ของเกษตรกรเลี้ยงปลาในบ่อดินที่ประสบความสำเร็จ จังหวัดอ่างทอง 2) ศึกษาเปรียบเทียบปัจจัยที่ส่งผลต่อความสำเร็จตามมาตรฐานกรมประมง (GAP) และเกณฑ์การประกวดเกษตรกรดีเด่นแห่งชาติ 3) ศึกษาเปรียบเทียบข้อมูลส่วนบุคคลกับปัจจัยการผลิตในการเพาะเลี้ยงปลาในบ่อดินตามมาตรฐาน GAP กับเกณฑ์การประกวดเกษตรกรดีเด่นแห่งชาติ และสร้างรูปแบบการเลี้ยงปลาในบ่อดินที่ประสบความสำเร็จในจังหวัดอ่างทอง กลุ่มตัวอย่างที่ใช้เป็นเกษตรกรเลี้ยงปลาในบ่อดินจังหวัดอ่างทอง จำนวน 300 ราย เก็บข้อมูลโดยแบบสอบถามและใช้สถิติค่าร้อยละ ค่าเฉลี่ยส่วนเบี่ยงเบนมาตรฐาน (S.D.) การวิเคราะห์ความแปรปรวน (one-way ANOVA) และค่าสถิติ t–test การสัมภาษณ์เชิงลึกและการสนทนากลุ่มผลการวิจัยพบว่า 1) ผู้ตอบแบบสอบถามเป็ นเพศหญิง ร้อยละ 55.3 มีอายุ 51-60 ปี ร้อยละ 36.3 มีการศึกษาระดับประถมศึกษา ร้อยละ 71.0 2) ปัจจัยที่ส่งผลให้ประสบความสำเร็จตามมาตรฐาน GAP อยู่ในระดับมาก 3) องค์ประกอบที่ส่งผลให้ประสบความสำเร็จตามเกณฑ์การประกวดเกษตรกรดีเด่นแห่งชาติอยู่ในระดับมาก 4) ผลการทดสอบสมมติฐานพบว่า ข้อมูลส่วนบุคคลที่แตกต่างกันส่งผลต่อองค์ประกอบความสำเร็จแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 จากข้อค้นพบในงานวิจัยได้รูปแบบการจัดการความรู้การเลี้ยงปลาในบ่อดินที่ประสบความสำเร็จในจังหวัดอ่างทองตามรูปแบบ CHRIT model คือ C=chooses (การคัดเลือกปัจจัยการผลิต), H=handle (การจัดการฟาร์ม), R=relation (ความสัมพันธ์กับชุมชน), I=idea (ความคิดริเริ่มสู่นวัตกรรม), T=tacit knowledge (ความรู้ในตัวเกษตรกร) Successful model of knowledge on fish farming management in earthen ponds at Angthong province The objectives of the study were 1) to study the knowledge management of fish farmers raising professionals in successful earthen pond in Angthong, 2) to compare the factors effecting the success of good agriculture practices (GAP), and 3) to compare the elements of the persons with inputs in fish farming management in the earthen pond and to study relationships between soil factors according to GAP on the basis of national outstanding farmer contest that resulted in successful farmers and initiate successful model of fish farming management in earthen ponds in Angthong. The 300 fishing farmers in Angthong were used to be the samples. The statistics used to analyze the data were percentage, frequency, mean, standard deviation (S.D.), one-way ANOVA, t-test, depth-interview and focus group. It was found from the study that, x) the respondents are 300 fishing farmers, most 55.3 percent of respondents are females at 55.3 percent, 36.3 percent are 51-60 years old atpeople 36.3 percent, 71.0 percent educated from elementary education at 71.0 percent, which are successful in Angthong at a high level. 2) The factors that result in successful according to GAP in the farmers’ practices raise fish in ponds in overall aspects is at a high level. 3) The elements on the basis of national outstanding farmer overall aspects are at a high level, and 4) hypothesis testing indicated that the personal information affected the elements of GAP and the contest farmers national award in differences differentat significance level of .01. From the findings of this study, successful model of knowledge on fish farming management in earthen ponds in Angthongis as CHRIT model : C=chooses, H=handle, R=relation, I=idea and T=tacit knowledge.